Implementation of the halal assurance system and MSME business development strategy: The case of a coffee shop - Muslich, Muhammad Ayyub; Nurhalim, Asep; Irfany, Mohammad Iqbal (Halal Studies and Society, 2024)
This study aimed to assist Micro, Small, and Medium Enterprises (MSMEs), specifically Dakara Coffee in meeting the requirements of the Halal Assurance System (HAS) 23000. Primary and secondary identification methods were used to implement the HAS Manual in this analysis. The HAS Manual which was designed for the specific conditions of Dakara Coffee comprised 11 criteria. The results showed that several identified food and beverage ingredients did not meet the HAS 23000 criteria and lacked supporting documents. Furthermore, several improvements were recommended such as replacing materials that did not comply with HAS 23000 and completing documentation for food and beverage ingredients. By using the Analytical Hierarchy Process (AHP) method, the primary priority for the business development of Dakara Coffee was identified as location, followed by other aspects including halal management, branding strategy, product innovation, and organizational management.